2021
DOI: 10.1177/0145482x211016918
|View full text |Cite
|
Sign up to set email alerts
|

Graphic Reading Performance of Students with Visual Impairments and Its Implication for Instruction and Assessment

Abstract: Introduction: The ability of students to engage with graphical materials supports learning in science, technology, engineering, arts, and mathematics areas. For students with visual impairments, understanding the factors that contribute to the effective interpretation of graphics can promote meaningful access to the curricula. Methods: Forty students with visual impairments completed multiple-choice question tasks for five types of graphics presented in their medium of choice and provided difficulty ratings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…Analysis of the think-aloud transcripts in this study connect with the quantitative findings reported elsewhere (see Zebehazy & Wilton, 2021). In Zebehazy and Wilton (2021), greater frequency of engaging with graphics and higher teacher ratings of independence with graphics were associated with higher performance on problems featuring graphics. In this study, higher performing students were more likely, during the think-aloud process, to indicate that they were relying on previous experience with a graphic type when solving a given problem as compared with lower performing students.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Analysis of the think-aloud transcripts in this study connect with the quantitative findings reported elsewhere (see Zebehazy & Wilton, 2021). In Zebehazy and Wilton (2021), greater frequency of engaging with graphics and higher teacher ratings of independence with graphics were associated with higher performance on problems featuring graphics. In this study, higher performing students were more likely, during the think-aloud process, to indicate that they were relying on previous experience with a graphic type when solving a given problem as compared with lower performing students.…”
Section: Discussionsupporting
confidence: 85%
“…Higher performers were better able to articulate strategy use and reasons for selecting strategies. Discussion: Findings coincide with quantitative findings of the participants (see Zebehazy & Wilton, 2021). Transcripts provided additional confirming evidence of the interdependence of MoGI components.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Our research extends previous research with students with visual impairments to explore whether younger students with visual impairment would benefit from a multimodal approach to understanding graphs they will later encounter formally in mathematics courses. Early and frequent engagement with graphs has been found to be a contributing factor to independence with graph reading (Zebehazy & Wilton, 2014a, in press). We hypothesize that a greater level of familiarity with these graphs and their significance may be helpful when such graphs are re-encountered later in school.…”
Section: Research Questionsmentioning
confidence: 99%